Unichamp Sdn. Bhd. / Zul Rusydi Hussin ... [et al.] - Hussin, Zul Rusydi; Abdullah, Nordin; Ahmad Nasram, Norhainasrah; Mustafa, Siti Khairiah; Mad Yusop, Mohd Fadli (Faculty of Sports Science and Recreation, 2000)
UNICHAMP Sdn. Bhd- was formed on January 2000 at Section 18, Shah Alam by Zul Rusydi B. Hussin, Norhainasrah Bt. AhmW-Nasram, Nordin B. Abdullah, Siti Khairiah Bt. Mustafa and Mohd. Fadli B. Mad Yusop. The Organization is fuUy own by Bumiputra. It's main business consist of Sports & Leisure Management Consultantcy.